Citizens' participation in small water resources development : a case study in the Northeast of Thailand - Taweechai Termkunanon; Weber, Karl E.; Goede, J.H. de; Angel, Shlomo; Dias, Hiran D.; King' s (Government of Thailand) (Bangkok : Asian Institute of Technology, 1979)
This study is an exploratory research and attempts to examine the existing patterns of traditional co-operation and to investigate the citizens 1 participation in small water resources development in Ban Huay Suag and Ban Huay Ton. The study is based on the previous study of 11A strategy for the development of small-scale water resources in the Northeast of Thailand11 conducted by the Asian Institute of Technology and the quantitative analysis of later data collected from Loei and Chaiyaphum. The study is divided into two parts, the practices of traditional co-operation and mutual help activities, the small water resources development in the study areas and the potential of adopting the patterns of traditional co-operation to the present small water resources development activities. The findings showed that the prospect of integration of the practices of traditional co-operation to the small water resources development activities is quite feasible.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Water resources development -- Thailand, Northeastern; Social participation -- Thailand, Northeastern